MARKETING DALAM PERSPEKTIF HUKUM ISLAM - H. Syahrul, H. Syahrul (DIKTUM: Jurnal Syariah dan Hukum, 2012)
Spiritual marketing is accomplished when the business we are able to provide happiness, honesty and fairness runs, whatever field were in. do not conflict with Islamic principles. Characteristics of Islamic marketing is: Rabbaniyyah, Akhlaqiyah, Al-waqiyyah, and human. Implementation of Marketing Sharia implemented when nine ethical marketing can be realized, namely: piety, Siddiq, Al-Adl, Khidmah, Al-Amanah, Suuzh-Zahn, backbiting, and do Riswah. Conventional marketing is free marketing value and not based on divine values in all marketing activities, marketers only focus on achieving set targets sellers. In Islamic marketing a must that every marketing activity he is always being watched by Allah, so be very careful in maintaining the marketing activities